FAKTOR-FAKTOR YANG MEMPENGARUHI MOTIVASI PENDONOR SUKARELA UNTUK MENDONORKAN DARAH DI UTD-PMI KRAMAT RAYA JAKARTA PUSAT - Laeli Farkhah; Marwan; Emil (STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2020)
The importance of the availability of blood was to meet the need for blood transfusions that could been occurred anytime such as for accident victims, patients with major surgery such as heart disease, cesarean section, and for patients with blood diseases such as hemophilia and thalassemia. Therefore, it was very important to know what are the factors that could affected someone to donate blood voluntarily and regularly. This research used descriptive quantitative. The number of respondents in this studied amounted to 43 people with Accidental Sampling as the sampling technique, where the respondent was a person who routinely donated blood every three months and at least three times to donate blood. The results are presented in frequency distribution table. The results showed that based on the characteristics of most respondents aged 36-45 years (48,8%), most respondents were male (79,1%), the largest respondents had high school (48,8%), most respondents worked as a self-employed (37,2%). The sources of information respondents still quite lacking. There were (55,8%) respondents that had medium knowledge. The attitude of the respondents considered good (100%). Reference group and the intention was contributed to the actions of respondents. The respondents had a good action to donate blood (52.3%). From the research results suggested that the UTD-PMI, Health Department and Department of Education to further enhance the promotion of blood donation to the community and to voluntary donors that expect to maintain and improve measures to donate blood.